EFEKTIVITAS MODEL PEMBELAJARAN PROBLEM BASED LEARNING (PBL) DALAM MENINGKATKAN KETERAMPILAN BERPIKIR KRITIS SISWA PADA MATERI FLUIDA STATIS - Ilham Adi Putra (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to determine the effect of the application of the Problem Based Learning (PBL) model on students' critical thinking skills in physics, specifically on the topic of static fluids, at Class XI of SMA Negeri 6 Padang. The low level of students’ critical thinking skills in physics learning served as the main issue in this research. A quasi-experimental method with a Nonequivalent Control Group Design was employed, involving two parallel classes: an experimental class taught using the PBL model and a control class taught using conventional learning. The research instrument was a validated and reliable essay test designed to assess critical thinking skills. Data were analyzed using an Independent Samples t-test after fulfilling normality and homogeneity tests. The results showed that the average critical thinking skill score in the experimental class was 81.70, while the control class scored 74.90. Hypothesis testing yielded a t-count of 4.82, which is greater than the t-table value of 1.99656 (α = 0.05), leading to the rejection of the null hypothesis. It can be concluded that the PBL model has a significant positive effect on students’ critical thinking skills. The implementation of PBL encourages students to actively engage in solving contextual problems, discussing in groups, and drawing conclusions critically.